Medium to long term follow up study of the efficacy of cessation of eye-rubbing to halt progression of keratoconus - Mazharian, Adrien; Flamant, Roxane; Elahi, Sina; Panthier, Christophe; Rampat, Radhika; Gatinel, Damien (Frontiers in Medicine, 2023)
Abstract: Purpose: To study the progression of keratoconus after cessation of eye rubbing with a minimum follow up of three-years. Design: Retrospective monocentric longitudinal cohort study of keratoconus patients with a minimum of three years follow-up. Participants: 153 eyes of 77 consecutive patients with keratoconus were included. Methods: Initial examination consisted of anterior and posterior segment evaluation using slit-lamp biomicroscopy. At the initial visit, patients were thoroughly informed of their pathology and instructed to stop rubbing their eyes. Eye rubbing cessation was assessed at all the follow-up visits at 6 months, 1 year, 2 years, 3 years and yearly afterward. Corneal topography using the Pentacam® (Oculus®, Wetzlar, Germany) was used to obtain maximum and average anterior keratometry readings (Kmax and Kmean), as well as thinnest pachymetry (Pachymin, μm) in both eyes. Main Outcome Measures: The main outcomes measured were maximum keratometry (Kmax), mean keratometry (Kmean), and thinnest pachymetry (Pachymin) values at various time points to assess for keratoconus progression. Keratoconus progression was defined as a significant augmentation of Kmax (>1D), Kmean (>1D), or significant diminution of Pachymin (>5%) throughout the total follow-up duration. Results: 153 eyes of 77 patients (75.3 % males) aged 26.4 years old, were followed for an average of 53 months. Over the course of the follow-up, there was no statistically significant variation of ∆Kmax (+0.04 ± 0.87; p=0.34), ∆ Kmean (+0.30 ± 0.67; p=0.27) nor ∆Pachymin (-4.36 ± 11.88; p=0.64). Amongst the 26 of the 153 eyes which had at least one criterion of KC progression, 23 admitted continuing eye rubbing, or other at-risk behaviors. Conclusions: This study suggests that a significant proportion of keratoconus patients are likely to remain stable if close monitoring and strict ARB cessation are achieved, without the need for further intervention.